(3aGYdjg HQfGeL bGFe Ydi GdSjchOQGeG dJMSjf GdEfJHGg dOi GdCWaGd GdeYGbjf YbdjG GdbGHdjf ddJYdje (B/s - (3,QVG eMeO Rci eMeO s; (3QVG eSYO GdLeGds; (3CMeO YHOGdQMje GdYeQjs; (3hdGA CMeO MSf NGdO s (2024)
(3gOaJ GdOQGSI GdMGdjI Edi GdJYQa aGYdjI HQfGeL bGFe Ydi GdSjchOQGeG dJMSjf GdEfJHGg dOj GdCWaGd GdeYGbjf YbdjkG GdbGHdjf ddJYdje , hGSJNOeJ GdHGMKI GdefgL THg GdJLQjHj dJMbjb CgOGa GdOQGSI , JchfJ YjfI GdOQGSI GdfgGFjI ef (B(10) (3GWkaGd (B(7 (3ef GdPchQ, (B3 (3ef GdGfGK(B)(3, JJQGhM CYeGQge GdRefjI eG Hjf (B(6 -9) (3SfhGJ ef GdCWaGd GdeYGbjf YbdjkG GdbGHdjf ddJYdje , hGTJedJ COhGJ GdOQGSI Ydi ebjGS SJGfahQO(B-(3Hjfjg ddPcGA (B((3GdUhQI GdNGeSI(B): ((3EYOGO LGd QhjO, JYQjH hJbfjjf eMehO CHh Gdfjd, (B2011) (3, ebjGS GdeSJhj GdGbJUGOj GdGLJeGYj GYOGO eMeO SYaGf hOYGA NWGH, ebjGS EfJHGg GdCWaGd hJhGabge(B:((3EYOGO YHO GdQbjH GdHMjQj hYaGa YLdGf(B) (3HGdEVGaI Edj HQfGeL bGFe Ydi GdSjchOQGeG(B. (3EYOGO (B((3GdHGMKI(B). (3hJhUdJ fJGFL GdOQGSI Edj hLhO aQhb OGdI EMUGFkjG Hjf eJhSWGJ QJH OQLGJ GdCWaGd CYVGA GdeLehYI GdJLQjHjI aj GdbjGSjf GdbHdj hGdHYOj HYO JWHjb GdHQfGeL GdbGFe Ydi GdSjchOQGeG aj JMSjf GdEfJHGg dUGdM GdbjGS GdHYOj, YOe hLhO aQhb OGdI EMUGFjkG Hjf eJhSWGJ QJH OQLGJ GdCWaGd aj GdbjGSjf GdHYOj hGdJJHYj HYO JWHjb HQfGeL GdSjchOQGeG hPdc Ydi ebjGS GdEfJHGg(B. (3eeG jTjQ Edj GSJeQGQ aGYdjI GdHQfGeL ceG XgQ ef fJGFL GdbjGS GdJJHYj, hbOeJ GdOQGSI eLehYI ef GdJhUjGJ hGdebJQMGJ dHMhK dGMbI(B.s
The current study aimed at identify the effectiveness of a psychodrama-based program on improving attention in educable mentally handicapped children. The researcher used the experimental method to achieve the study$1 (Bs objectives. The final study sample consisted of 10 children (7 boys and 3 girls) aged between 6 and 9 years. The study tools included the Stanford-Binet Intelligence Scale (Fifth Edition) (prepared by Gale Roid, adapted and standardized by Mahmoud Abu El-Nil, 2011), the Socioeconomic Status Scale (prepared by Mohamed Saafan and Doaa Khattab), the Attention Deficit Hyperactivity Disorder Scale (prepared by Abdel Raqeeb Al-Bahiri and Mostafa Al-Hadibi), and a psychodrama-based program (prepared by the researcher) Results: The study found statistically significant differences between the mean ranks of the children$1 (Bs scores in the pre- and post-tests after applying the psychodrama-based program, in favor of the post-test. There were no statistically significant differences between the mean ranks of the children$1 (Bs scores in the post-test and the follow-up test on the attention scale, indicating the continued effectiveness of the program as shown by the follow-up results. The study provided a set of recommendations and suggestions for further research.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B96-121.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdGWaGd HWjFh GdJYdes; (3GdGWaGd GdThGPs; (3GdSjchOQGeG s -- (3GdEfJHGgs -- (3GdCWaGd GdeYGbjf YbdjGs